Wabi-Sabi: is it the winning factor in darts? / Nur Ilianis Adnan, Isma Noornisa Ismail and Mah Boon Yih - Adnan, Nur Ilianis; Ismail, Isma Noornisa; Mah, Boon Yih (Academy of Language Studies, 2023)
A Japanese aesthetic principle known as wabi-sabi emphasizes impermanence, imperfection, and the majesty of the natural world. Contrarily, darts is a game that requires skill and precision. Is it possible to connect the two vastly different concepts? By representing APB in a recent friendly Dart match, we began to understand the connections. You could approach playing darts with a wabi-sabi mindset. Instead of aiming for perfect land, you could embrace the imperfections that come with the game. For example, rather than getting frustrated when you miss the bullseye, you could appreciate the way the dart landed on the board in a unique and imperfect way because it is not all the time that you must hit big numbers. Sometimes (especially towards the end), missing the bullseye is a blessing. Why, you may ask? Let’s get to the basics of darts. The game starts with a score of 501. The score for each turn is calculated and deducted from the players’ total. You will win the game once you become the first to reduce the score to exactly zero. Hence the need to strategize by missing the bullseye, or even the dart board to avoid the score from ‘burst’ if you get higher scores. Now, is it clearer why missing the board is a blessing? By letting go of the need for perfection, you may find yourself enjoying the game more and feeling less pressure to perform.